Identifikasi dan Penetapan Kadar Formalin pada Tahu Putih di Lima Pasar Daerah Jakarta Timur dengan Metode Spektrofotometri Visible - Mayasari, Yeshi; Purwanitiningsih, Eny; Sugiantari, Nining (Universitas Mohammad Husni Thamrin, 2024)
Tofu is a food source of protein that is widely consumed by the public. The high vegetable protein content in tofu is considered to be able to replace animal protein. According to the Food and Drug Supervisory Agency (BPOM), formalin is currently widely misused as a preservative in food products such as tofu. The Indonesian government has also banned the use of formaldehyde as a food preservative since 1982. Examination of the presence of formaldehyde in white tofu sold in five markets in the East Jakarta area was carried out qualitative tests using chromatopathic acid reagent and quantitative tests to determine levels. The research sample consisted of 18 samples from five markets in the East Jakarta area. Based on the research results, it can be concluded that of the 18 white tofu samples, 11 were positive and 7 were negative for containing formalin. Qualitative test results showed that 4 samples from the Cibubur market were 100% positive (5.85 ppm), 3 samples from the Obor market were 100% positive (5.62 ppm), 3 samples from the Kramat Jati main market were 100% positive (25.07 ppm), 4 samples from the Ciracas market were 25% positive (0.44ppm). The long-term goal is not to use formalin as a preservative in tofu. Special targets provide information to the public about the dangers of formaldehyde used as a preservative. The research method uses a direct research design during the period May–June 2023. The target output is published in a nationally accredited journal. Keywords: White Tofu, Formalin, Visible Spectrophotometry